The oxalyl‐CoA synthetase‐regulated oxalate and its distinct effects on resistance to bacterial blight and aluminium toxicity in rice. (7th February 2017) - Peng, C.; Liang, X.; Liu, E.‐E.; Zhang, J.‐J.; Peng, X.‐X.
Abstract: Oxalic acid is widely distributed in biological systems and known to play functional roles in plants. The gene AAE3 was recently identified to encode an oxalyl‐CoA synthetase (OCS) in Arabidopsis that catalyses the conversion of oxalate and CoA into oxalyl‐CoA. It will be particularly important to characterise the homologous gene in rice since rice is not only a monocotyledonous model plant, but also a staple food crop. Various enzymatic and biological methods have been used to characterise the homologous gene. We first defined that AAE3 in the rice genome ( OsAAE3) also encodes an OCS enzyme. Its K m for oxalate is 1.73 ± 0.12 mm, and V m is 6824.9 ± 410.29 U·min −1 ·mg protein −1 . Chemical modification and site‐directed mutagenesis analyses identified thiols as the active site residues for rice OCS catalysis, suggesting that the enzyme might be regulated by redox state. Subcellular localisation assay showed that the enzyme is located in the cytosol and predominantly distributed in leaf epidermal cells. As expected, oxalate levels increased when OCS was suppressed in RNAi transgenic plants. More interestingly, OCS‐suppressed plants were more susceptible to bacterial blight but more resistant to Al toxicity. The results demonstrate that the Os AAE3 ‐encoded protein also acts as an OCS in rice, and may play different roles in coping with stresses. These molecular, enzymatic and functional data provide first‐hand information to further clarify the function and mechanism of OCS in rice plants.